PENERAPAN TERAPI KOMPLEMENTER KOMPRES HANGAT JAHE MERAH PADA LANSIA UNTUK MENURUNKAN SKALA NYERI RHEUMATOID ARTHRITIS DI WILAYAH KERJA UPTD PUSKESMAS MUNJUL JAYA PURWAKARTA - Herwed Nelson; Serly, Serly; Desi, Desi (Bajang Institute, 2023)
Rheumatoid Arthritis is a systemic autoimmune disease in sufferers of the joints of the hands and feet which experience joint inflammation, which causes swelling. Pain can cause damage to the joints. It is estimated that around 1.7 billion people experience problems with the musculoskeletal system and it is estimated that this will increase in the next 10 years. Rheumatoid Arthritis sufferers are 35% in Purwakarta Regency. This research uses Pre-Experimental quantitative research with a One-Group Pretest Posttest design. The results of research using warm red ginger compresses which were carried out for 5 days and within 15 minutes each day for one respondent, there was a decrease, initially on a scale of 5 and on the last day to a scale of 3. From the results of the research conducted by researchers, it was in line with the journals taken and there was a decrease by applying a warm red ginger compress. Based on the results of the bivariate analysis, the mean pain before the warm compress was applied was 5.57 ± 1.73, while the average pain after the warm compress was applied was 3.80 ± 1.42. Based on the results of statistical tests using the Paired Samples Test, it was found that ρ value = 0.000, with a value of α = 0.05 (ρ < α), meaning that there was an effect of warm compresses with ginger on the intensity of pain in elderly people with rheumatoid arthritis at the 23 Ilir Palembang Health Center. 2022 with an average score difference of 1.77